Control of expression and activity of peroxisome proliferated‐activated receptor γ by Annexin A1 on microglia during efferocytosis. (3rd September 2019) - da Rocha, Gustavo Henrique Oliveira; Loiola, Rodrigo Azevedo; Pantaleão, Lorena do Nascimento; Reutelingsperger, Chris; Solito, Egle; Farsky, Sandra Helena Poliselli
Abstract : Annexin A1 (AnxA1) is a protein secreted by phagocytic cells which plays a pivotal role on the resolution of inflammation by enhancing phagocytosis carried out by phagocytes. Which factors and intracellular mechanisms are linked to such actions exerted by AnxA1 are yet to be completely understood. In order to investigate such, BV2 microglial cells were transfected with plasmids aimed at down‐modulating AnxA1 expression and also treated with exogenous recombinant rAnxA1; gene and protein expression of proliferated‐activated receptor γ (PPARγ) and CD36, STAT6 phosphorylation and phagocytosis of apoptotic neurons were investigated. Down‐modulating AnxA1 in BV2 cells impaired gene and protein expression of PPARγ, effects reversed by treatment with recombinant AnxA1 (rAnxA1). Lower levels of CD36 were also verified in AnxA1 down‐modulated BV2 cells. AnxA1‐mediated phagocytosis of apoptotic cells was abrogated due to blockade of PPARγ activation, and in AnxA1 down‐modulated cells exogenous AnxA1 failed to exert any effects on phagocytosis. Lower levels of STAT6/pSTAT6 in AnxA1 down‐modulated BV2 cells suggest the involvement of this transcription factor with PPARγ and CD36 synthesis and actions. Data here shown suggest that there is a probable connection between AnxA1, PPARγ, and CD36, which must all act in association in order for efferocytosis to occur properly. AnxA1‐mediated phosphorylation of STAT6 is probably involved with intracellular pathways involving PPARγ and CD36 actions. These data evidence that PPARγ/CD36 play a role on AnxA1‐mediated efferocytosis in microglial cells. Significance of the study: The findings of this work provide evidence that the glucocorticoid‐mediated protein annexin A1 modulates PPARγ expression and that PPARγ is important for annexin A1‐mediated efferocytosis. Only recently the interaction between these two factors has begun to be explored, and knowledge on associated cell mechanisms are still scarce. Elucidating how annexin A1 and PPARγ interact with one another provides basis for further research aimed at understanding molecular pathways and cell signaling events involved with these factors, expanding existing knowledge on the anti‐inflammatory effects of such factors.